Early community-based teaching of medical undergraduates for achieving better working skills in the community - Himashree Bhattacharrya; Gajendra Kumar Medhi; Star Pala; Amrita Sarkar; Ophelia Mary Kharmujai; Wallambok Lynrah (Wolters Kluwer Medknow Publications, 2018)
INTRODUCTION: It has been perceived that there is a lack of community exposure and active learning in the community for the first-year undergraduates in Community Medicine. This study is designed to evaluate an early community exposure given to the students to help overcome these lacunae. METHODOLOGY: In this study, the first-year students (n = 44) were provided an early community exposure and evaluated to understand their perceptions by a prevalidated, pre- and post exposure questionnaire. The community exposure was given to the students by allocating them families in community with designated tasks A core group of mentors monitored the students and scored the students on every visit. Attendance of students, scores marked by the mentors, and pre- and postexposure responses were used to evaluate the impact of community exposure. RESULTS: A total of 44 students were evaluated in this study. A total of 22 h (36.6%) were dedicated to community-based learning in the 1st year. A positive response was observed in the postexposure responses with regard to the understanding of the subject and interest in the subject in comparison to preexposure responses (P < 0.05). A statistically significant difference was observed in the first and final visit scores by the mentors with respect to communication skills, elicitation of history, team spirit, and attitude toward community (P < 0.00001). CONCLUSIONS: Students were exposed to the concept of community service and inculcated an interest in public health. Early community exposure of medical undergraduate students is important in developing better working skills in the community.